Infiltrasi Pendidikan Agama dan Budaya di Indonesia: Perspektif Islam dan Barat - Fahmy, Achmad (Pendidikan Agama Islam, 2019)
This article wants to examine the relationship between religious education and culture in Indonesia from an Islamic and Western perspective. This view stems from the assumption that culture is a human product that provides space for humans freely without regard to religious values. In detail, this article wants to describe a number of things, namely: First, conflict at the level of discourse between religious and cultural education in Indonesia; Second, religious education in a cultural context; Third, Islamic and Western perspectives on religious and cultural education. In discussing this article, the author uses a qualitative library research methodology whose main object is in the form of library materials, articles, journals, and other literature.